OPEN SESSIONS ON LANDSCAPE: verso un nuovo modello di formazione al progetto paesaggistico - Falqui, Enrico (Ri-Vista. Research for landscape architecture, 2016)
“Landscape is not architecture, urbanism , agronomy, ecology, and is not geography, or semiotics, or engineering ... but it is all at the same time, in an increasingly different location combination for the place, its properties being obvious or hidden, shout or reticent” (Zagari, 2013). The intellectual and professional figure of landscaper of which there is need today, it should be a designer figure with specific knowledge and skills that are related to the construction of the space itself. However, these skills have become so strictly defined and specific, it can no longer only be formed through a general culture but require, now, an university education of first, second and third cycle. Open Sessions on Landscape, is a project of 10 international conferences promoted by PhD in Landscape Architecture of Florence, and it was born as a ‘tool’ in-depth knowledge both of the major schools of European and extra-European Landscape Architecture, both the innovations methodological, conceptual and representation of the construction processes of the landscape project in the various systems and territorial contexts.